Developing critical global citizenship: Vocational reflection in international learning experiences. (26th April 2022) - Ooi, Su‐Mei
Abstract: This chapter argues that the challenge to global education lies in helping students develop critical global citizenship and suggests that the high‐impact practice of vocational reflection can change misplaced attitudes toward the purpose of global engagement.